2011
DOI: 10.1177/107769901108800404
|View full text |Cite
|
Sign up to set email alerts
|

How Production Value Impacts Perceived Technical Quality, Credibility, and Economic Value of Video News

Abstract: Although media professionals use production value to refer to technical aspects of program quality, evidence suggests that viewers are not adept at recognizing this property of content. Nonetheless, broadcasters are attempting to differentiate news product based on technical dimensions. To test the utility of this strategy, this experiment examined how production value impacts perceived technical quality, credibility, and economic value across two age cohorts. Viewers recognized variation in production value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…Although technical excellence, associated to taste and aesthetics (Bottomley, 2015), has been considered in the concept of quality television more frequently when analysed from the perspective of professionals such as program creators, members of juries and television reviewers, viewers can also form their own opinion. Although they may lack the expertise to assess this aspect in detail, they have the ability to make general appraisals, detect extremely high and low technical quality and are sensitive to production value when assessing quality (Cummins & Chambers, 2011). For instance, a large-scale survey among television users in Israel found that although the audience is not very good at discerning gradations of production value among different programs and genres, technical characteristics explain television program appreciation and quality evaluations" among viewers (Shamir, 2007).…”
Section: Meaning Of Quality Television For Viewersmentioning
confidence: 99%
“…Although technical excellence, associated to taste and aesthetics (Bottomley, 2015), has been considered in the concept of quality television more frequently when analysed from the perspective of professionals such as program creators, members of juries and television reviewers, viewers can also form their own opinion. Although they may lack the expertise to assess this aspect in detail, they have the ability to make general appraisals, detect extremely high and low technical quality and are sensitive to production value when assessing quality (Cummins & Chambers, 2011). For instance, a large-scale survey among television users in Israel found that although the audience is not very good at discerning gradations of production value among different programs and genres, technical characteristics explain television program appreciation and quality evaluations" among viewers (Shamir, 2007).…”
Section: Meaning Of Quality Television For Viewersmentioning
confidence: 99%
“…Credibility of news has also been shown to be related to elements associated with sensory stimulation, such as visual presentation, personalities, aesthetic presentation, and audiovisual factors (Bracken, 2006;Cummins & Chambers, 2011;Lee, 1978;Slater & Rouner, 1996). For example, Cummins and Chambers (2011) suggest that visual news presentation might offer better source credibility than other forms while Bracken (2006) found the quality of images presented on television contributed to audience credibility. Moreover, in earlier studies, Lee (1978) found that the pictures and personalities associated with the visual presentation influenced credibility, moreover, while Slater and Rouner (1996) discovered that aesthetic presentation and content also enhance perceptions of credibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Production techniques such as pacing (Lindekugel, 1994, p. 136) or sound effects associated in a tabloid style news presentation are not deemed newsworthy by audiences compared to standard presentational styles (Grabe, Zhou, Lang, & Bolls, 2000). Lang, Potter, and Grabe (2003) found that certain production techniques used in writing (e.g., Cummins & Chambers, 2011) and editing were likely to enhance the enjoyability, informativeness, and believability of news stories. Production techniques are part of the aesthetic dimensions, which may include "shot composition or framing, continuity editing or the effective use of lighting to convey emotional tone" (Cummins & Chambers, 2010, p. 5).…”
Section: Uses and Gratificationsmentioning
confidence: 99%
“…can be defined as depth of scrutiny" (p. 694). However, measurements of quality of technical criteria (Cummins & Chambers, 2011) have yet to be explored from the perspective of elements of newsgathering techniques (Diefenbach, 2008;Headley, 2013).…”
Section: Defining Qualitymentioning
confidence: 99%